2008
DOI: 10.1186/1471-2164-9-204
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence and rapid evolution of the rice pathogen Xanthomonas oryzae pv. oryzae PXO99A

Abstract: BackgroundXanthomonas oryzae pv. oryzae causes bacterial blight of rice (Oryza sativa L.), a major disease that constrains production of this staple crop in many parts of the world. We report here on the complete genome sequence of strain PXO99A and its comparison to two previously sequenced strains, KACC10331 and MAFF311018, which are highly similar to one another.ResultsThe PXO99A genome is a single circular chromosome of 5,240,075 bp, considerably longer than the genomes of the other strains (4,941,439 bp a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
226
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(234 citation statements)
references
References 66 publications
(73 reference statements)
5
226
0
3
Order By: Relevance
“…oryzae and strain BLS256 for X. oryzae pv. oryzicola (11,12,14,32). Nontarget bacterial DNAs were pooled in equimolar concentrations, with the DNA from 10 strains included in each pool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…oryzae and strain BLS256 for X. oryzae pv. oryzicola (11,12,14,32). Nontarget bacterial DNAs were pooled in equimolar concentrations, with the DNA from 10 strains included in each pool.…”
Section: Methodsmentioning
confidence: 99%
“…oryzae and two strains of X. oryzae pv. oryzicola are publicly available (GenBank accession numbers AYSX00000000 and AYSY00000000, respectively) (11)(12)(13)(14). These resources, along with draft genome sequences of another nine X. oryzae strains, provided insights into the genetic diversity among strains within this species, including a unique group of weakly pathogenic X. oryzae strains isolated in the United States (13; V. Verdier, unpublished).…”
mentioning
confidence: 99%
“…3B). In addition to the numerous regulatory loci that map elsewhere in the Xanthomonas genomes (16)(17)(18)(19)(20), our findings highlight the existence of key regulatory loci that map within the hrp-hrc-hpa genes in X. oryzae pv. oryzicola.…”
Section: Discussionmentioning
confidence: 94%
“…In xanthomonads, the hrp-hrc-hpa genes are highly conserved and clustered within several sequenced genomes (16)(17)(18)(19)(20). Our previous studies revealed that the hrp cluster in X. oryzae pv.…”
mentioning
confidence: 99%
“…citri, X. campestris pv. campestris, Xanthomonas perforans have been documented (Kim et al, 2009;Lee et al, 2005;Ochiai et al, 2005;Salzberg et al, 2008), only a few of them have been studied extensively for their functional role in disease induction (AkimotoTomiyama et al, 2012;Bartetzko et al, 2009;Kim et al, 2009;Kumar and Mondal, 2013;Mondal et al, 2016;Song and Yang, 2010). The Indian Xoo strain has been studied recently in details for their composition of T3SS effectors.…”
Section: Discussionmentioning
confidence: 99%